2023
DOI: 10.3389/fped.2022.1060843
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a multicenter, double-blind, randomized, placebo-controlled phase III trial of the inhaled β2-adrenergic receptor agonist salbutamol for transient tachypnea of the newborn (the REFSAL trial)

Abstract: BackgroundTransient tachypnea of the newborn (TTN), which results from inadequate absorption of fetal lung fluid, is the most common cause of neonatal respiratory distress. Stimulation of β-adrenergic receptors enhances alveolar fluid absorption. Therefore, the β2-adrenergic receptor agonist salbutamol has been proposed as a treatment for TTN. This study aims to evaluate the efficacy and safety of salbutamol as supportive pharmacotherapy together with non-invasive nasal continuous positive airway pressure (NIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Neonates delivered at or near term (at gestational age > 34 weeks) may have hypoxic respiratory failure due to a variety of problems, including congenital diaphragmatic hernia (CDH), pneumonia or sepsis, aspiration of meconium, respiratory distress syndrome, and primary persistent pulmonary hypertension [ 11 ]. In addition to ECMO, conventional treatment includes oxygen support, mechanical breathing, alkalosis induction, neuromuscular blockade, and sedation.…”
Section: Introductionmentioning
confidence: 99%
“…Neonates delivered at or near term (at gestational age > 34 weeks) may have hypoxic respiratory failure due to a variety of problems, including congenital diaphragmatic hernia (CDH), pneumonia or sepsis, aspiration of meconium, respiratory distress syndrome, and primary persistent pulmonary hypertension [ 11 ]. In addition to ECMO, conventional treatment includes oxygen support, mechanical breathing, alkalosis induction, neuromuscular blockade, and sedation.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that fetal alveolar fluid, which fills the airways and alveoli in the intrauterine period, affects the lung mechanics positively by stretching the lungs. This fluid needs to be cleaned in order for effective gas exchange to take place after birth [ 2 ]. The main mechanism in TTN is thought to be delayed absorption of fetal alveolar fluid in the perinatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Since these channels are not activated or being immature at birth, the fluid in the lungs cannot be absorbed and leads to a decrease in respiratory functions of infants after birth. It has been shown that the expression of ENaC subunits is low in late preterm and term infants with transient neonatal tachypnea [ 1 , 2 , 4 ]. Decreased surfactant function has been also shown to contribute to the pathophysiology of TTN.…”
Section: Introductionmentioning
confidence: 99%